Numerical modelling and experimental validation of the behaviour of brick masonry walls subjected to blast loading. (February 2021) - Chiquito, M.; Castedo, R.; Santos, A.P.; López, L.M.; Pérez-Caldentey, A.
Highlights: Detailed micro-modelling approach seems adequate for modelling a very complex problem The LOAD_BLAST_ENCHANCED command provides adequate values of applied pressures The model is able to capture failure mode and accelerations with good approximation Remanent displacements after blast show, as expected, larger differences Abstract: Masonry walls are one of the most common elements used in all kinds of buildings around the world. Due to the brittle composition of these elements, they may represent a hazard when an explosion occurs. This research is conducted to investigate the performance of different protective solutions applied on brick masonry walls subjected to blast loads. The contribution is focused on the search for a numerical model that can accurately reproduce an explosive event and be used as a prediction tool for the design of buildings against explosions. A numerical model using a detailed micro-modelling approach has been developed for this purpose including non-reinforced walls as well as carbon fibre and glass fibre reinforced walls. The results of the different scenarios simulated are compared with the field test data (six different tests) in terms of pressure, acceleration, and permanent displacements. The results show that the model is reliable. For the retrofitted walls the plastic displacements are slightly underestimated (by less than 10% of the wall depth) but the predicted global response is acceptable in all the cases studied, involving different explosive charges, different protective solutions and mortars of different strength. Graphical abstract: Image, graphical abstract